Antimalarial drug toxicity: a review. - Taylor, W; White, N (2004)
Malaria, caused mostly by Plasmodium falciparum and P. vivax, remains one of the most important infectious diseases in the world. Antimalarial drug toxicity is one side of the risk-benefit equation and is viewed differently depending upon whether the clinical indication for drug administration is malaria treatment or prophylaxis. Drug toxicity must be acceptable to patients and cause less harm than the disease itself. Research that leads to drug registration tends to omit two important groups who are particularly vulnerable to malaria--very young children and pregnant women. Prescribing in pregnancy is a particular problem for clinicians because the risk-benefit ratio is often very unclear. The number of antimalarial drugs in use is very small. Despite its decreasing efficacy against P. falciparum, chloroquine continues to be used widely because of its low cost and good tolerability. It remains the drug of first choice for treating P. vivax malaria. Pruritus is a common adverse effect in African patients. As prophylaxis, chloroquine is usually combined with proguanil. This combination has good overall tolerability but mouth ulcers and gastrointestinal upset are more common than with other prophylactic regimens. Sulfadoxine/pyrimethamine is well tolerated as treatment and when used as intermittent preventive treatment in pregnant African women. Sulfadoxine/pyrimethamine is no longer used as prophylaxis because it may cause toxic epidermal necrolysis and Stevens Johnson syndrome. Mefloquine remains a valuable drug for prophylaxis and treatment. Tolerability is acceptable to most patients and travellers despite the impression given by the lay press. Dose-related serious neuropsychiatric toxicity can occur; mefloquine is contraindicated in individuals with a history of epilepsy or psychiatric disease. Quinine is the mainstay for treating severe malaria in many countries. Cardiovascular or CNS toxicity is rare, but hypoglycaemia may be problematic and blood glucose levels should be monitored. Halofantrine is unsuitable for widespread use because of its potential for cardiotoxicity. There is renewed interest in two old drugs, primaquine and amodiaquine. Primaquine is being developed as prophylaxis, and amodiaquine, which was withdrawn from prophylactic use because of neutropenia and hepatitis, is a potentially good partner drug for artesunate against falciparum malaria. Atovaquone/proguanil is a new antimalarial combination with good efficacy and tolerability as prophylaxis and treatment. The most important class of drugs that could have a major impact on malaria control is the artemisinin derivatives. They have remarkable efficacy and an excellent safety record. They have no identifiable dose-related adverse effects in humans and only very rarely produce allergic reactions. Combining an artemisinin derivative with another efficacious antimalarial drug is increasingly being viewed as the optimal therapeutic strategy for malaria.